Microvessel density (MVD) and cyclooxygenase-2 (COX-2)/β-catenin interaction are associated with relapse in patients with transitional carcinoma receiving adjuvant chemotherapy with paclitaxel/carboplatin: A hellenic Cooperative Oncology Group (HECOG) st - Bamias, A.; Kyriakou, F.; Chorti, M.; Kavantzas, N.; Noni, A.; Kyroudi-Voulgari, A.; Rontoyianni, D.; Kastritis, E.; Xiros, N.; Patsouris, E.S.; Murray, S.; Tamvakis, N.; et al. (Anticancer Research, 2008)
Background: Cycloxygenase (COX)-2 has been associated with proliferation, apoptosis and angiogenesis in urothelial cancer. The prognostic significance of COX-2 in patients who received adjuvant chemotherapy for urothelial cancer was examined. Patients and Methods: Expression of COX-2, p53, ki67, β-catenin, vascular endothelial growth factor (VEGF) and microvessel density (MVD) were studied retrospectively in 59 patients with urothelial cancer (pT3, pT4, N+) who had undergone surgery. The patients had subsequently received adjuvant chemotherapy. Results: Thirty-eight out of 59 cases (64% ) were positive for COX-2. COX-2 was not associated either with progression-free survival (PFS) or overall survival (OS). MVD levels ≥47 were associated with longer median PFS compared with lower levels (not reached vs. 13 months [95% CI: 8-18], p=0.048). The median PFS for patients with β-catenin nuclear accumulation and COX-2 expression was 6 months (95% CI: 4-7) compared with 19 months (95% CI: 14-23) for neither or only one of these factors (p=0.018). Conclusion: MVD may be a useful indicator of relapse in high-risk urothelial cancer treated with adjuvant chemotherapy.
Keywords: Bladder cancer; CD105; COX-2; MVD; β-Catenin